Labrador Inuit on the Hunt: Seasonal Patterns, Techniques, and Animals as They Appear in the Early Moravian Diaries - Olsthoorn, Thea (Études Inuit Studies)

(untitled) (Centre interuniversitaire d’études et de recherches autochtones (CIÉRA), 2017)
In 1769 an Order in Council from the British government enabled the Moravians to settle in Labrador. The missionaries laid the boundary stones for their land (ca. 405 km2) in the next year, and established their first mission station (Nain) on the Labrador coast in 1771. The brethren’s accounts of their experiences with the Inuit in the Nain diaries include, besides religious issues, weather and travel reports and descriptions of Inuit hunting grounds and hunting techniques for the fauna of the region. This article focuses on their diary depictions of the two main prey species: the seal and the caribou. Consideration is also given to seasonal variation and availability of these animals during the early years of the mission; data were collected for the years 1771 through 1778. Several clues in the Moravian diaries, which went unrecognized by the missionaries, point to interactions and transformations between human and nonhuman beings (animals, spirits). These indications corroborate the spiritual transgression of category boundaries as an essential feature of traditional hunting methods.